A RESECTED CASE OF JUVENILE PROGRESSIVE DUODENAL CANCER - YAMAMOTO, Seiichi; SUMITANI, Naotaka; HIROSAWA, Hisashi; FUKUSHIMA, Wataru; IZUMI, Ryohei; SAITO, Katsuhiko (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2003)
We report a case of juvenile onset of progressive duodenal cancer in a 26-year-old man. Upper gastrointestinal endoscopy for his complaint of upper abdominal pain showed a narrowing due to ulcerative lesion at the duodenal bulb. A biopsy resulted in poorly differentiated adenocarcinoma. Surgical findings showed H0P1N1S1 (panc.), and a pancreatoduodenectomy and D2 lymph node dissection were performed with resection of peritoneal dissemination as possible as we could, resulting in a curability B. At the same time, a peritoneal Infuse-A-port was subcutaneously indwelt in the abdomen. After the operation, FP regimen was sustained for 8 months, but 22 months after the operation, the patient experienced intestinal obstruction due to peritonitis carcinomatosa. Although adjuvant therapy was changed to MTX/5FU regimen, the regimen was withdrawn due to aggravation of his general condition and only 250 mg of 5FU per day was administered. Thereafter no remission of intestinal obstruction was gained except a stable condition, and the patient died one year nine months after the operation. Juvenile progressive duodenal cancer is so rare that only five cases including this case have been reported in Japan.